The relationship between optimal knee flexion angle and hamstring flexibility: Indication for hamstring strain injury - Liu, H.; Wan, X.; Garrett, W. E.; Yu, B. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to determine the relationships among hamstring flexibility, optimal knee flexion angle for maximal knee flexion moment, maximal knee flexion moment. Ten male and 10 female reactional athletes were tested for hamstring flexibility and isokinetic strength. The maximal knee flexion moment and the knee flexion angle corresponding to the maximal knee flexion moment were determined for each participant. Optimal knee flexion angle was a function of hamstring flexibility score and gender, but not of the hamstring strength. Optimal knee flexion angle and hamstring strength were not correlated. These results indicate that hamstring muscle optimal length is correlated to its flexibility, but not to its strength. Increased hamstring flexibility is correlated with increased muscle optimal length. Hamstring flexibility may be a risk factor for hamstring strain injury.